SOCIO-CULTURAL DYNAMICS AND IDENTITY IN CONTEMPORARY PAPUAN COMMUNITIES - Yanto Wenda; Jhonson Rumainum; Samuel Mambor; Peter Wenda (International Journal of Education and Social Science Studies, 2025)
This study explores the socio-cultural dynamics and identity formation processes within contemporary Papuan communities amid rapid modernization, globalization, and political change. Drawing on qualitative data from field observations, interviews, and document analysis, the research highlights how Papuans negotiate their cultural heritage and social identity in the face of external influences such as state policies, religious conversion, and digital media proliferation. Findings reveal that Papuan identity is not static but fluid, characterized by adaptive strategies that blend traditional values with modern realities. The role of Christianity, youth activism, and social media emerges as critical in shaping new expressions of ethnic identity. However, challenges persist due to uneven implementation of autonomy policies and tensions between development initiatives and cultural preservation. This study contributes to a nuanced understanding of indigenous resilience, emphasizing the need for inclusive and culturally sensitive governance approaches in Papua. The implications underscore the importance of recognizing indigenous agency in shaping social and political futures.